2017
DOI: 10.1101/mcs.a001537
|View full text |Cite
|
Sign up to set email alerts
|

SPG20 mutation in three siblings with familial hereditary spastic paraplegia

Abstract: Troyer syndrome (MIM#275900) is an autosomal recessive form of complicated hereditary spastic paraplegia. It is characterized by progressive lower extremity spasticity and weakness, dysarthria, distal amyotrophy, developmental delay, short stature, and subtle skeletal abnormalities. It is caused by deleterious mutations in the SPG20 gene, encoding spartin, on Chromosome 13q13. Until now, six unrelated families with a genetically confirmed diagnosis have been reported. Here we report the clinical findings in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Intriguingly, the brother in our study was diagnosed with Troyer syndrome combined with GHD, a phenomenon that has never been reported before. Most patients with Troyer syndrome have been observed to have mild atrophy of the vermiform lobe and hyperintensity of white matter around the ventricles on T2‐weighted imaging on brain MRI, but some patients have normal brain MRI findings . Our findings indicate that 84.2% of patients have abnormal brain MRIs, so MRI is valuable for diagnosis.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Intriguingly, the brother in our study was diagnosed with Troyer syndrome combined with GHD, a phenomenon that has never been reported before. Most patients with Troyer syndrome have been observed to have mild atrophy of the vermiform lobe and hyperintensity of white matter around the ventricles on T2‐weighted imaging on brain MRI, but some patients have normal brain MRI findings . Our findings indicate that 84.2% of patients have abnormal brain MRIs, so MRI is valuable for diagnosis.…”
Section: Discussionmentioning
confidence: 71%
“…Many studies have reported that these patients have delayed milestones; however, because of their severe and progressive neurological symptoms, their short stature has not received much attention. 13,20 Our study focused on the issue and found most of these patients had extremely short stature.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Spartin is conserved throughout multicellular eukaryotes, although expressed in all tissues, it seems to be of particular importance in neurons. This may explain the HSP-associated symptoms in the absence of the protein 2 3 4 5 6 . The medical relevance of spartin goes beyond neurodegeneration, since the epigenetic silencing via hypermethylation of SPG20 is associated with colorectal and gastric cancer.…”
Section: Introductionmentioning
confidence: 99%